Matriona Ivnako tells several stories - Matriona Ivnako; Anatoly Sorokin; Valentina Dedyk (Alexander King, 2013)
Matriona tells several myths and some other stories. Just a short pause after previous video finished. Plus ambient audio recording. Also fluent (listening, reading, some writing/speaking) in English and Japanese. Alutor level is elementary. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra.